Improvement of Pollen Production and Seed Yield in Male Parent (CB 174R) and Rice Hybrid CORH 4 - S SEETHALAKSHMI; R JERLIN (Seed Research, 2026)
The present investigation was undertaken to standardize techniques to improve the pollen production in male parent and to enhance the seed yield of rice hybrid CORH 4. The male parent of rice hybrid CORH 4 i.e., CB 174R was given different methods of staggering and foliar sprays. Different staggering methods includes alternate planting of the staggered male parent (Planting of first staggered seedlings in 1" row at 30 cm spacing, planting of second staggered seedlings at 2nd row at 30 cm spacing and planting of third staggered seedlings in both the rows at 15 cm spacing), planting of three staggered seedlings by dividing the male rows into three equal parts and mixed planting of the male parent in single hill. Foliar sprayings were given as boron spray @ 0.02% and ZnSO4 spray @ 0.5% at boot leaf stage. The result of this study indicated that among various staggering methods, mixed planting of three staggered seedlings in a single hill along with application of boron (0.02%) as foliar spray at boot leaf stage enhanced the pollen viability (97.5%), pollen germination (66.6%) and pollen tube growth (150.6µ) in male parent. The seed yield recorded was maximum (1031.2 kg/ha) in mixed planting of the three staggered seedlings coupled with the foliar spraying of boron (0.02%), as compared to control (610.2 kg/ha).